State-of-the-art Review of Metallic Microneedles: Structure, Fabrication, and Application - Zhishan Yuan; Hongzhao Zhang; Wentao Hu; Xiao Yu; Si Qin; Chengyong Wang; Fenglin Zhang (Chinese Journal of Mechanical Engineering)
Abstract Microneedle (MN) is a medical device containing an array of needles with a micrometer-scale. It can penetrate the human stratum corneum painlessly and efficiently for treatment and diagnosis purposes. Currently, the materials commonly used to manufacture MNs include silicon, polymers, ceramics and metals. Metallic MNs (MMNs) have drawn significant attention owing to its superior mechanical properties, machinability, and biocompatibility. This paper is a state-of-the-art review of the structure, fabrication technologies, and applications of MMNs. According to the relative position of the axis of MN and the plane of the substrate, MMNs can be divided into in-plane and out-of-plane. Solid, hollow, coated and porous MMNs are also employed to characterize their internal and surface structures. Until now, numerous fabrication technologies, including cutting tool machining, non-traditional machining, etching, hot-forming, and additive manufacturing, have been used to fabricate MMNs. The recent advances in the application of MMNs in drug delivery, disease diagnosis, and cosmetology are also discussed in-depth. Finally, the shortcomings in the fabrication and application of MMNs and future directions for development are highlighted.